KUALITAS APLIKAIS MOBILE JKN TERHADAP KEPUASAN PENGGUNA DI BPJS KESEHATAN CABANG SINGARAJA - NURKARIANI, NI LUH; WIRANDANI, KOMANG AYU ALIT (GANEC SWARA, 2024)
The purpose of this study is to determine the level of satisfaction of BPJS Health Singaraja Branch users regarding the quality of the JKN mobil application. The survey used in this research used quantitative methods.  The implementation of this research took place at BPJS Health Singaraja Branch. The research sample was random. Data collection was carried out using a questionnaire which was distributed directly to the community using the JKN mobile application. We chose 100 people who used the Mobile JKN application as respondents. The analytical method used in this research is the SPSS version 18 model. All relationships investigated show significant positive results in terms of service quality, system quality and information quality, which influence user satisfaction of the JKN mobile application. For this reason, BPJS Health Singaraja Branch is expected to be able to improve the quality of the application so that it remains an online administration tool. The realization of user satisfaction will have an impact on the survival of the BPJS Health Singaraja Branch which is influenced by Service Quality, System Quality and Information Quality from the Mobile JKN application itself.